1979
DOI: 10.1111/j.1532-5415.1979.tb01725.x
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Folate Levels in Young and Old

Abstract: Erythrocyte folate levels were compared among 25 young healthy subjects (mean age, 27 years), 29 healthy subjects aged over 75 living in the community, 62 subjects (mean age, 75) admitted to a geriatric assessment ward (acute illnesses), and 32 subjects (aged over 65) in a ward for long-term physical or mental illnesses. Overall, the female/male sex ratio varied from 2:1 to 3:1. For the three elderly groups, the incidence of low erythrocyte folate levels (less than 100 mmicrogram/100 ml) were 24 percent, 16 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Our data are also limited by the fact that no central laboratory was used in the CSHA. Red blood cell folate is a better measure of tissue levels than serum folate, which is more sensitive to abrupt changes in intake [60]. Our analyses were also restricted to baseline folate measures and there may have been significant changes in these levels during follow-up related to changes in dietary intake and/or use of vitamin supplements.…”
Section: Discussionmentioning
confidence: 99%
“…Our data are also limited by the fact that no central laboratory was used in the CSHA. Red blood cell folate is a better measure of tissue levels than serum folate, which is more sensitive to abrupt changes in intake [60]. Our analyses were also restricted to baseline folate measures and there may have been significant changes in these levels during follow-up related to changes in dietary intake and/or use of vitamin supplements.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin B 12 deficiency occurs in 10-20% (Nilsson-Ehle, 1998), folate deficiency in 3-19% (Webster & Leeming, 1979;Joosten et al, 1993;Matthews, 1995). Vitamin B 6 might be more important for normal P-tHcys than previously appreciated (McKinley et al, 2001), but sometimes causes elevated P-tHcys only after methionine loading (Ubbink et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators have found a decrease in the serum vitamin B 12 level in the aged 19,20 whereas others have found that the serum B 12 level remains constant throughout life 21,22 . Similarly, in some studies, measurements of serum and erythrocyte folate concentration in the aged have shown that the level is unchanged, 21,23 whereas in other studies these concentrations have been shown to decrease with age 24–25 . Assays of vitamin B 12 or folate have certain disadvantages.…”
Section: Discussionmentioning
confidence: 99%